2016
DOI: 10.1002/bjs.10286
|View full text |Cite
|
Sign up to set email alerts
|

National study of the impact of patient information and involvement in decision-making on immediate breast reconstruction rates

Abstract: BackgroundReconstructive alternatives should be discussed with women facing mastectomy for breast cancer. These include immediate and delayed reconstruction, which both have inherent advantages and disadvantages. Immediate reconstruction rates vary considerably in Swedish healthcare regions, and the aim of the study was to analyse reasons for this disparity.MethodsAll women who underwent mastectomy for primary breast cancer in Sweden in 2013 were included. Tumour data were retrieved from the Swedish National B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 33 publications
(35 reference statements)
1
40
0
Order By: Relevance
“…Some existing studies suggested that hospitals and/or surgeons act as gatekeepers to BR access and that inter‐hospital variations may not be ‘purely resource‐driven’ . In NSW, surgeons must be accredited by a hospital in order to be granted operating privileges and lists at that particular hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Some existing studies suggested that hospitals and/or surgeons act as gatekeepers to BR access and that inter‐hospital variations may not be ‘purely resource‐driven’ . In NSW, surgeons must be accredited by a hospital in order to be granted operating privileges and lists at that particular hospital.…”
Section: Discussionmentioning
confidence: 99%
“…In the previously reported study of a similar cohort, younger age, non‐invasive tumours, no clinically involved lymph nodes and residence in the Stockholm/Gotland region were independent predictors of undergoing IBR, as well as the availability of in‐house plastic surgery services, patient information and involvement in decision‐making. This raised the question of whether the observed regional differences could be associated with differences in socioeconomic factors.…”
Section: Resultsmentioning
confidence: 69%
“…Significant regional differences in IBR rates in Sweden have been reported previously 19 , and were not explained by regional differences in tumour or patient characteristics, but by disparities in patient information, availability of plastic surgery services and patient involvement in decision-making. As socioeconomic factors were not taken into account at that time, the aim of the present study was to determine their potential association with IBR rates, as well as with patient-reported information and involvement in the surgical decision-making process.…”
Section: Introductionmentioning
confidence: 54%
“…Post‐mastectomy reconstruction has been shown to improve satisfaction and psychological outcomes for women following mastectomy, yet due to the elective nature of the procedure, it is particularly susceptive to disparities in uptake . Most of the previous research regarding the unequal rates of uptake of reconstruction has focused on racial/ethnic disparities, but there is an increasing focus on patient needs for reliable information and engagement in the shared decision‐making process . Patients with LHL represent a unique population that require tailored interventions specific to their health literacy level and preferred learning style.…”
Section: Discussionmentioning
confidence: 99%